PEMAHAMAN KONSEPTUAL MATEMATIS SISWA DALAM MATERI BANGUN RUANG SISI DATAR DI SEKOLAH MENENGAH PERTAMA - Sinthia, Desti; Sugiatno, Sugiatno; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research to determine student’s conceptual understanding of Flat Side Solid figure in junior high school. This study used qualitative desciptive method. Data was collected using tests, interviews, and documentation. The subjects of this research were 6 of 30 grade VIII B students of Junior High School 11 Pontianak which were determined by the results of the student’s conceptual understanding tests. The results of the tests showed that student’s mathematical conceptual understanding was classified as moderate with a percentage of high ability (16.66%), moderate ability (66,66%), and low ability (16,66%). Categorization based on indicators that achieved in the conceptual understanding test. The high category with the achievement of four indicators, the moderate category with the achievement of two to three indicators, and the low category with achievements did not answer correctly.Keywords: Conceptual Understanding, Level Of Ability